A study on the cold workability and shape memory effect of NiTiHf-Nb eutectic high-temperature shape memory alloy. (December 2020) - Chen, Jie; Zhang, Shengwang; Zhang, Yonghao; Zhang, Ji; Wen, Yuhua; Yang, Qin; Huang, Shuke; Wang, Xiebin
Abstract: In this work, we report a (Ni50.1 Ti34.9 Hf15 )85 Nb15 alloy that shows excellent cold workability and good high-temperature shape memory effect. The as-cast sample shows eutectic microstructure consisting of β-Nb and the NiTiHf(Nb) matrix. The homogenized (Ni50.1 Ti34.9 Hf15 )85 Nb15 alloy shows high compressive fracture strain of 40% and excellent cold-rolling reduction ratio of 80%. It is suggested that the formation of (semi-) coherent β-Nb is the main reason on improving the ductility of NiTiHf alloy. After solution treatment, the material shows a high martensitic transformation start temperature of 146 °C, and a maximum shape memory effect strain of 2.3%. This work demonstrates that (Ni50.1 Ti34.9 Hf15 )85 Nb15 alloy with good cold workability and high-temperature shape memory effect may provide new opportunities for applications. Highlights: Microstructure comprises (semi-) coherent β-Nb and NiTiHf(Nb) matrix is obtained. Coherent β-Nb acts as nucleation and promotes martensitic transformation. Compressive fracture strain 40% and cold-rolling reduction ratio 80% are obtained. Martensitic transformation start temperature of 146 °C is obtained. A maximum shape memory effect strain of 2.3% is achieved.